The moderating role of externalizing problems on the association between anxiety and the error‐related negativity in youth. Issue 4 (2nd August 2020) - Suor, Jennifer H.; Granros, Maria; Kujawa, Autumn; Fitzgerald, Kate D.; Monk, Christopher S.; Phan, K Luan; Burkhouse, Katie L.
Abstract: The error‐related negativity (ERN) is an event‐related potential that reflects error monitoring. Enhanced ERN indicates sensitivity to performance errors and is a correlate of anxiety disorders. In contrast, youth with externalizing problems exhibit a reduced ERN, suggesting decreased error monitoring. Anxiety and externalizing problems commonly co‐occur in youth, but no studies have tested how comorbidity might modulate the ERN. In a sample of youth ( N = 46, ages 7–19) with and without anxiety disorders, this preliminary study examined the interactive effect of anxiety and externalizing problems on ERN. Results suggest that externalizing problems moderate the relation between anxiety symptoms and ERN in youth. Anxious youth with less externalizing problems exhibited enhanced ERN response to errors. Conversely, anxious youth with greater externalizing problems demonstrated diminished ERN in response to errors. The regions of significance and proportion affected tests indicated that the moderating the effect of externalizing problems was only significant for youth with anxiety disorders. Findings suggest that enhanced neural error sensitivity could be a specific neurophysiological marker for anxiety disorders, whereas anxious individuals with comorbid externalizing problems demonstrate reduced error monitoring, similar to those with primary externalizing pathology. Results underscore the utility of examining neural correlates of pediatric anxiety comorbidity subtypes.